2021
DOI: 10.3390/cells10010098
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of PRIMA-1 and PRIMA-1Met (APR246) in Hematological Malignancies: Still a Mutant P53-Dependent Affair?

Abstract: Because of its role in the regulation of the cell cycle, DNA damage response, apoptosis, DNA repair, cell migration, autophagy, and cell metabolism, the TP53 tumor suppressor gene is a key player for cellular homeostasis. TP53 gene is mutated in more than 50% of human cancers, although its overall dysfunction may be even more frequent. TP53 mutations are detected in a lower percentage of hematological malignancies compared to solid tumors, but their frequency generally increases with disease progression, gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 96 publications
0
29
0
Order By: Relevance
“… 8–10 wtp53 promotes cell cycle arrest and apoptosis, and also inhibits VEGF-dependent angiogenesis, thereby countering rapid tumor growth, metastasis, and possible drug resistance. 6 , 11 , 12 Upon induction of apoptosis, wtp53 may be rapidly localized to the mitochondria in order to induce mitochondrial outer membrane permeabilization (MOMP), leading to the release of pro-apoptotic factors from the intermembrane space. 10 wtp53 also plays an important role in the DNA damage response, senescence, DNA repair, cell migration and autophagy.…”
Section: P53 Tumor Suppressor: Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8–10 wtp53 promotes cell cycle arrest and apoptosis, and also inhibits VEGF-dependent angiogenesis, thereby countering rapid tumor growth, metastasis, and possible drug resistance. 6 , 11 , 12 Upon induction of apoptosis, wtp53 may be rapidly localized to the mitochondria in order to induce mitochondrial outer membrane permeabilization (MOMP), leading to the release of pro-apoptotic factors from the intermembrane space. 10 wtp53 also plays an important role in the DNA damage response, senescence, DNA repair, cell migration and autophagy.…”
Section: P53 Tumor Suppressor: Structure and Functionmentioning
confidence: 99%
“… 11 Furthermore, mtp53 protein is not recognized and is therefore no longer regulated by the MDM2 negative feedback loop, leading to mtp53 protein accumulation. 12 Studies show that the mtp53 protein conformation is stabilized through interactions with proteins such as heat shock protein 90 (HSP90), or as a result of post-translational modifications, such as phosphorylation at the Ser20 and Thr180 residues. In addition, its failure to induce MDM2 activation may also play a role in the stabilization of mtp53 protein.…”
Section: P53 Tumor Suppressor: Structure and Functionmentioning
confidence: 99%
“…APR-246, which is clinically effective in prostate and hematological cancers [ 37 ], was also shown to inhibit growth and metastatic potential of TNBCs by several studies [ 38 , 39 ]. Although APR-246 has been well studied in the context of mutant p53, more recent data suggests that it has an independent role in both wild-type and p53 null contexts [ 22 , 40 ]. Notably, both inhibitors as single agents, under our study conditions, failed to show either a mutant P53- or subtype-specific association.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it was found that the compound PRIMA-1 (MET) can restore transcriptional activity of some mutant forms of TP53, a homolog of TP63 (Bykov et al, 2002). In fact, PRIMA-1 (MET) is currently being tested in a phase III clinical trial for the treatment of certain myelodysplastic syndromes in which patients carry TP53 mutations, and is being explored for therapeutic use in other malignancies (Menichini et al, 2021). Based on structural similarities between TP53 and TP63, studies to investigate the potential for PRIMA-1 (MET) to restore the function of mutant TP63 proteins were conducted.…”
Section: Potential Therapies For Aec and Eecmentioning
confidence: 99%